Fundo Nacional de Desenvolvimento Regional: impactos na economia do Ceará - Dias, Erika Nunes (2024)
This study aims to analyze the impact of the implementation of the National Fund for Regional Development - FNDR, created by Constitutional Amendment No. 132, of December 20th 2023, which instituted the reform of the national tax system, on public investments in the State of Ceará. A specific and careful empirical exercise is proposed here that allows analyzing and quantifying the values that will be distributed to the State of Ceará, if the criteria adopted by the constituent legislator remain unchanged until the first transfer of the FNDR value by the Union. Based on the values obtained and the application parameters, it is possible to analyze the effects and impacts of the resource on public investments in the State of Ceará.